This is your captain speaking : my fantastic voyage through Hollywood, faith, & life - MacLeod, Gavin, 1931-; Dagostino, Mark (Nashville, Tennesee : W Publishing Group, an imprint of Thomas Nelson, 2013)
The remarkable life, career, and faith journey of the star of? The Love Boat? and? The Mary Tyler Moore Show . For 16 years, millions of Americans welcomed Gavin MacLeod into their living rooms every Saturday night. This veteran of stage and screen transformed himself from a seasoned?character actor into the leading, lovable father-figure of? The Love Boat ?at the height of TV's boom years. For more than 30 years, Gavin MacLeod has served as the global ambassador for Princess Cruises. Speaking to thousands of travelers each year, and signing hundreds of autographs at every port, he stands poised to celebrate his amazing journey with a look back at the golden era of American television. The consummate storyteller, Gavin shares his fondest memories of meeting and working with countless stars, such as Cary Grant, Steve McQueen, Gregory Peck, Bette Davis, Frank Sinatra, Ethel Merman, Ella Fitzgerald, Ronald Reagan, Milton Berle, and Fred Astaire. From his humble theatrical beginnings in upstate New York, to Radio City Music Hall and on to Hollywood, Gavin MacLeod was on the fast track to success. However, a few hard life lessons?like dealing with a divorce?taught Gavin that the key to happiness was only through a deep faith in God, and he feels his work for Christ is more important than any award. Three years later his remarriage proved that a great struggle can culminate in a happy ending
Keywords: MacLeod, Gavin, -- 1931-; Television actors and actresses -- Biography